Rancangan Sistem Informasi Kepatuhan Minum Obat Malaria dalam Menunjang Penerapan Sistem Kepatuhan Minum Obat pada Pasien Malaria Tertiana (Journal of Telenursing (JOTING), 2023)
This study aims to explore the experiences of malaria patients regarding medication adherence and design a model for medication adherence in malaria patients. This research method is qualitative research with an action research approach. The study results produced a design for SIPENGUAT (Medicine Taking Reminder Information System). The conclusion is that the client's experience regarding compliance with taking medication was that the client did not comply/completely consume Primaquin medication for 14 days because he forgot, was healthy, and took the medicine for a long time. This research produced a design for an information system for adherence to taking malaria medication, namely SIPENGUAT. Keywords: Compliance, Malaria, Design